Endurance. Attitudes/behaviors, performance in athletes and potential health effects (Sports and athletics preparation, performance, and psychology, 2014)
Cardiorespiratory endurance is both a health-related and sport-related physical fitness component due to its association with health and well-being, and sports performance, respectively. Since the number of those participating in regular endurance training is continuously increasing, it is very interesting to explore performance, as well as the psychological and health aspects of endurance. This book attempts to address performance, psychological and health aspects of cardiorespiratory endurance. In this collective volume, we have tried to provide a background for understanding various aspects of endurance to the readers. We are thankful to all the authors for their valuable contributions. In addition, we thank the reviewers who corrected the chapters, and the staff of Nova Publishers for their valuable suggestions. (novinka)